(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Low convergences of H 2 O 2 could be created through the electrochemical change of oxygen by applying an electric potential to a conductive framework and produce a low, yet steady, centralization of H 2 O 2 that would be adequate to demolish biofilms. To test our theory we utilized a multidrug-safe Acinetobacter baumannii strain, since this species is regularly ensnared in hard to-treat biofilm contaminations.